China's "New Normal": An Interpretation from Institutional and Marxian Views. Issue Volume 16:Issues 1(2017) (2nd January 2017) - Suzuki, Yasushi; Miah, Mohammad Dulal
ABSTRACT: China is approaching towards a new phase of economic development which is frequently termed as the "new normal". The paper aims to interpret China's "new normal" from the New Institutional Economics and Marxian viewpoints. The former school is primarily concerned with the "supply-side" driver of increasing economic output and efficiency. It advocates for free and open markets for ideas to sustain China's economic growth or advance itself into a global centre of technological innovation or scientific discovery. The Marxian view, on the other hand, shares the concern of "demand-side" driver of increasing economic output. Also, it calls for the shift from consumption-led to investment-led strategy while maintaining an egalitarian pattern of income distribution for successful transition. The paper argues that China is gradually advancing its capacity for innovation facilitated by in-house and foreign investments. However, the growing income inequality may pose a threat to its soft landing.